Comprehensive Performance Optimization in KNN-Based Piezoelectric Ceramics for an Ultrasonic Transducer - Han, Yu; Guan, Shangyi; Xie, Lixu; Zhang, Kun; Yang, Tinghao; Quan, Yi; Xing, Jie; Fei, Chunlong; Tan, Zhi; Webber, Kyle Grant; Zhu, Jianguo (Inorganic Chemistry, 2025)
Potassium sodium niobate (KNN) ceramics, characterized by their high Curie temperature (TC), favorable piezoelectric coefficients, and relatively low density, represent an environmentally friendly alternative to lead-based piezoelectrics. The fundamental challenge lies in simultaneous optimization of their piezoelectric performance─particularly piezoelectric coefficient d33and electromechanical coupling coefficient kp─while preserving both thermal stability and TC. Herein, a targeted doping strategy is proposed to optimize the composition of the KNN-based ceramics. The controlled acceptor doping in the multiphase coexistence system enables the regulation of grain size, and the disturbance of the long-range ordered structure leads to the formation of nanodomains, which further enhance the piezoelectric response. Excellent densification and uniform microstructure contribute to both high TCand enhanced piezoelectric performance while ensuring stability across varying temperatures and frequencies. The optimized composition (x = 0.4) achieves exceptional piezoelectric properties: d33= 358 pC/N and kp= 56.6%. In addition, it demonstrates a TCof 315 °C and good thermal stability. The optimized KNN-based ultrasonic transducer exhibits a 3.19 MHz center frequency with 60% bandwidth (−6 dB) and achieves high-resolution imaging, demonstrating excellent signal transduction capabilities suitable for mid-to-high frequency ultrasonic devices and energy harvesting application